PREVALÊNCIA DE DERMATOSES EM ESCOLARES EM UM DISTRITO INDUSTRIAL, SÃO LUÍS-MARANHÃO - AMORIM, Nilgicy Maria de Jesus (2015)
Cross-sectional analytical study with a quantitative approach, in order to determine the prevalence of skin diseases in school children in Vila Maranhão, in São Luís, Maranhão. Data were collected between the months of March 2014 to February 2015. Clinical data were recorded in a specific record, subsequently built a database. To verify the relationship and distribution of their frequencies between variables we used the chi-square test and Fischer's exact test. The significance level for all tests was α ≤ 0.05 to 95% confidence interval.The total number of schoolchildren covered by the survey was 930 and 393 schoolchildren aged 6-21 years. Pediculosis and Vesicolor pityriasis were the most prevalent infectious skin diseases. It was observed that pediculosis was more frequent in females. Acne vulgaris is the most frequent in the age group 13-21 years. While Pediculosis and vesicolor pityriasis were more frequent in the age group 6-12 years. Despite the proximity of industries with the schoolchildren housing, morbid conditions were not identified and it can be attributed directly to industrial pollutants.